Primary classical Hodgkin lymphoma of rectum: Report of an extremely rare case and review of the literature - Jayasudha Arundhathi Vasudevan; Rekha A Nair; K Rakul Nambiar (Wolters Kluwer Medknow Publications, 2017)
Hodgkin lymphoma (HL) commonly presents as nodal disease, but in a subset of cases, the disease primarily develops in extranodal sites. Primary classical HL of the gastrointestinal (GI) tract is an extremely rare occurrence. Primary nature of the disease is confirmed after a complete lymphoma work up including chest radiograph, computed tomography scan, peripheral blood, and bone marrow studies. Only a few cases of primary GI lymphomas with limited immunohistochemical or molecular confirmation have been reported in literature. We report the case of a 64-year-old immunocompetent woman with primary rectal HL. She presented with constipation, and on sigmoidoscopy examination, she was detected to have an ulceroproliferative circumferential growth in the rectum. Considering the possibility of rectal carcinoma, a low anterior resection was done. Histology was suggestive of mixed cellularity classical HL. She was started on combination chemotherapy, and she responded well to treatment. However, she developed pulmonary complication after the fourth cycle of chemotherapy and succumbed to the illness. Primary rectal HL is extremely rare, and to the best of our knowledge, only 16 cases have been reported previously. We believe that reporting this case will add to the scarce data about this unusual presentation in immunocompetent patients.